Convergences, transferts et intégrations entre sciences du langage, sciences et ingénierie en temps de guerre et de guerre froide (1941-1966) - Jacqueline Léon (Revue d’Histoire des Sciences Humaines)
This paper aims at examining the impact of war sciences on language sciences during the World War II. I will assume that the interaction between war sciences (engineering and sciences) and language sciences should be distinguished from the war effort undertook by linguists to teach foreign languages. Two cases will be analyzed. Roman Jakobson’s distinctive features theory, associating acoustical physics and information theory to linguistics, led to a new phonology in continuity with phonetics. Machine translation, as a cold war technology conceived outside of linguistics, initiated the second mathematics turn of language, that is the mathematics and computer turn of language sciences. In both cases, one will examine which type of connection between war sciences and linguistics is concerned : transfer, convergence or integration.